Solubility Enhancement of Carvedilol by Solid Dispersion Technique Using Sodium Alginate, Guar Gum, Xanthan Gum, and Locust Bean Gum as Polymers - Iyan Sopyan; Nurdiani Adiningsih; Sandra Megantara; Siska Sari Marvita (Indonesian Journal of Chemistry, 2023)
Carvedilol (CVD) is a non-selective β-blocker. CVD is included in BCS class II. It has low water solubility. In this research, solid dispersion was used to increase the solubility and dissolution profile of CVD. In silico study using the ligand-ligand docking method. The preparation of solid dispersion using the kneading method with a weight ratio of 1:1, 1:2, 1:3, and 1:4, evaluation of solid dispersion includes solubility and dissolution. The best solid dispersion was characterized using FTIR, DSC, and PXRD. In silico study showed complexes CVD-SA, CVD-GG, CVD-XG and CVD-LBG have a hydrogen interaction. SA and XG were chosen as carriers in solid dispersion. CVD solid dispersion showed increased solubility in all samples, with the highest increase at 90.63 times at CVD: XG (1:4). The results of the dissolution profile obtained at 60 min are 64.95 ± 0.45% at pure CVD, 83.32 ± 1.19% at CVD:SA (1:4), and 72.56 ± 3.62% at CVD: XG (1:4). The FTIR spectrum indicates an interaction between CVD and SA. The thermogram indicated the amorphous drug, and the diffractogram showed a decrease in crystallinity. Solid dispersion is proven to increase the solubility and dissolution profile of CVD. Solid dispersion CVD: SA (1:4) showed the highest solubility and dissolution profile.